Hydrogen enhanced cracking via dynamic formation of grain boundary inside aluminium crystal. (1st May 2021) - Xie, De-Gang; Wan, Liang; Shan, Zhi-Wei
Graphical abstract: Highlights: In situ bending tests of single crystalline Al in environmental TEM were performed. Low angle GB formed at crack tip on loading with or without hydrogen atmosphere. Cracking is much more easy along the low angle GB formed with hydrogen atmosphere. GBs have much stronger HEDE effect and a high potency for H atoms segregation. Dynamic formation of GBs can be key for H-induced transgranular cracking of metals. Abstract: By in situ bending tests inside an environmental transmission electron microscope, we found that from the pre-crack tip of single crystalline aluminium cantilevers, dislocations are emitted and self-organized to build a low angle grain boundary (LAGB), along which the crack propagates more easily in hydrogen atmosphere than in vacuum. Atomistic modelling suggests that the LAGB formed can strongly trap hydrogen atoms, and its cohesive strength can be substantially reduced. These results imply that the hydrogen-induced transgranular crack in a polycrystalline metal can proceed by repeating a process of dynamically forming a hydrogenated LAGB and its subsequent separation in grain.